2018
DOI: 10.1186/s12893-018-0442-z
|View full text |Cite
|
Sign up to set email alerts
|

Use of retrieval bag in the prevention of wound infection in elective laparoscopic cholecystectomy: is it evidence-based? A meta-analysis

Abstract: BackgroundSurgical site infections complicate elective laparoscopic cholecystectomies in 2,4-3,2% of cases. During the operation the gallbladder is commonly extracted with a retrieval bag. We conducted a meta-analysis to clarify whether its use plays a role in preventing infections.MethodsInclusion criteria: elective cholecystectomy, details about the gallbladder extraction and data about local or systemic infection rate. Exclusion criteria: cholecystitis, jaundice, concurrent antibiotic therapy, immunosuppres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 33 publications
0
14
0
2
Order By: Relevance
“…No one method has been shown to be superior to another. 2 In an attempt to reduce costs, we began to use sterile, unpowdered, latex-free surgical gloves for retrieval. We found no disadvantage to their use.…”
Section: Introductionmentioning
confidence: 99%
“…No one method has been shown to be superior to another. 2 In an attempt to reduce costs, we began to use sterile, unpowdered, latex-free surgical gloves for retrieval. We found no disadvantage to their use.…”
Section: Introductionmentioning
confidence: 99%
“…Complications from bile and gallstone spillage are rare according to large studies looking at overall outcomes of laparoscopic cholecystectomies [[17], [18], [19]]. Regina and colleagues [20] recently performed a meta-analysis, which demonstrated that retrieval bags do not reduce the rate of infection during gallbladder extraction. However, their paper excluded cases of cholecystitis and suspected carcinoma, presenting a biased perspective against retrieval bags.…”
Section: Discussionmentioning
confidence: 99%
“…They also stated that lack of association between the bile and causing WI organisms suggests that WI does not depend on direct contact of the GB while extraction, instead the skin commensals play a part in it. 35 Neri et al compared two groups for PSI with and without topical AB and found out that the incidence of umbilical port site infection is less compared to the non-topical AB groups. In their trial, they applied Rifamycin after the closure of the wound at the end of the surgery and at 12, 24, 36, 48 and 72 hours maintaining full sterility.…”
Section: On the Other Hand Those Who Are In Support Of Abp Argue Thatmentioning
confidence: 99%